2012
DOI: 10.1080/13607863.2012.688191
|View full text |Cite
|
Sign up to set email alerts
|

Stressful life events and daily stressors affect awakening cortisol level in midlife mothers of individuals with autism spectrum disorders

Abstract: Objectives The current study examines the awakening cortisol level in midlife mothers (M=51.4 years old, SD=8.4) of individuals (M=22.1 years old, SD=7.1) with autism spectrum disorders (ASD) under stressful conditions that are not specific to the son or daughter's ASD symptoms. Methods In addition to completing a set of questionnaires and in-home interviews, 82 mothers from the Adolescents and Adults with Autism Study (AAA) participated in a Daily Diary Study. Results Findings from the multilevel models i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 50 publications
3
35
0
Order By: Relevance
“…The finding is consistent with the literature on individuals with a history of PTSD indicating that despite lower overall levels, they may exhibit an elevated cortisol response to stressful events that are distinct from the original trauma (e.g., Bremner et al, 2003; Heim et al, 2001); by analogy, work stressors are distinct from child-related stress for mothers of individuals with DD. This study focused on nonfamily work stress and thus extends prior research on blunted or flattened cortisol patterns in the context of child- or family-related stress for parents of sons or daughters with disabilities (e.g., Seltzer et al, 2009; Seltzer et al, 2010; Wong et al, 2012). The results position us to better understand how different sources of stressors affect the health and physiology of adults experiencing a sustained life of emotional and personal demands (i.e., parenting an adolescent or adult offspring with a disability).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The finding is consistent with the literature on individuals with a history of PTSD indicating that despite lower overall levels, they may exhibit an elevated cortisol response to stressful events that are distinct from the original trauma (e.g., Bremner et al, 2003; Heim et al, 2001); by analogy, work stressors are distinct from child-related stress for mothers of individuals with DD. This study focused on nonfamily work stress and thus extends prior research on blunted or flattened cortisol patterns in the context of child- or family-related stress for parents of sons or daughters with disabilities (e.g., Seltzer et al, 2009; Seltzer et al, 2010; Wong et al, 2012). The results position us to better understand how different sources of stressors affect the health and physiology of adults experiencing a sustained life of emotional and personal demands (i.e., parenting an adolescent or adult offspring with a disability).…”
Section: Discussionmentioning
confidence: 83%
“…Although there are different approaches to examining cortisol, including the complete daily rhythms, this study focuses on awakening cortisol levels, consistent with our prior analysis of the effects of stressful life events and daily stress in mothers of children with ASD (Wong et al, 2012). The morning cortisol level reflects the body’s ability to mobilize energy to handle the tasks of the day (Clow, Thorn, Evans, & Hucklebridge, 2004).…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…[32,40] Moreover, the possibility of a "switch" from HPA-axis hyper-to hypofunction, although in accordance with Selye's original "general adaptation syndrome," [41] as well as with more recent neurobiological stress models [42,43] including McEwen's allostasis paradigm, [44,45] awaits further empirical research. Particularly, it should be clarified under which particular conditions (epigenetic consequences of victimization, role of precedent depression, inadequate coping, duration of illness, interference of physical factors …) such a HPA-axis "switch" could occur (see in this context, e.g., [46][47][48]). …”
Section: Introductionmentioning
confidence: 99%
“…In the general population, stressful life events have been found to be adversely associated with chronic diseases such as heart disease, diabetes, obesity and depression (Barry & Petry, 2008; Cutrona et al, 2005; Engstrom, Hedblad, Rosvall, Janzon, & Lindgarde, 2006; Engstrom et al, 2004; Kendler, Karkowski, & Prescott, 1999; Pyykkonen et al, 2010). Recent studies have also found that stressful life events were positively associated with individual biological markers such as cortisol concentration (Karlen, Ludvigsson, Frostell, Theodorsson, & Faresjo, 2011; Wong et al, 2012) and with increased odds for metabolic syndrome (Raikkonen, Matthews, & Kuller, 2007). However, limited evidence exists for the effect of stressful life events on multisystem dysregulation, such as that captured by a composite measure of allostatic load, which may precede harmful health outcomes (McEwen & Stellar, 1993; Seeman, Singer, Rowe, Horwitz, & McEwen, 1997).…”
Section: Introductionmentioning
confidence: 99%